Analisis Potensial Energi Terbarukan dengan Pemetaan Quantum Gis-Based di Desa Karangpring - Faizin, Nur; Wibowo, Michael Joko; Febriani, Siti Diah Ayu; Qanitah (JSED, 2026)
This research aims to map areas with renewable energy potential and product diversification for solar power plants (PLTS), microhydro, and biogas in the Karangpring Village Jember Regency. The research was conducted throughout Jember Regency from March to September 2025. The mapping was conducted through a combination of digitization (database and spatial data analysis using Quantum GIS), surveys, and public consultations as a map correction process. This research was conducted in five stages: potential identification using secondary data, field surveys, data collection and acquisition, spatial data analysis, and map layout. The area of Karangpring Village is 1,259,435 hectares, consisting of four hamlets: Krajan, Durjo, Gendir, and Karangpring. The population of Karangpring Village is 7,772, and the majority are farmers. Based on geographical data, Karangpring village is located at 8°04'57.9"-8°08'11.9" South Latitude and 113°38'38.3"-113°40'22.3" East Longitude. Karangpring Village has relatively high renewable energy potential: 1,232 MWh from biogas, 10.54 MWh from wind, and 52,934 MWh/m2 from solar energy. Durjo Hamlet is the largest hamlet and has the largest renewable energy generation potential: 266.76 kWh from biogas, 3.4 MWh from wind, and 13,076 MWh/m2 from solar energy.